The male external urethral sphincter is autonomically innervated. Issue 2 (22nd December 2020) - Nyangoh Timoh, Krystel; Moszkowicz, David; Creze, Maud; Zaitouna, Mazen; Felber, Margaux; Lebacle, Cédric; Diallo, Djibril; Martinovic, Jelena; Tewari, Ashutosh; Lavoué, Vincent; Ghukasyan, Gevorg; Benoit, Gerard; et al.
Abstract: Introduction: The aim of the present study was to describe autonomic urethral sphincter (US) innervation using specific muscular and neuronal antibody markers and 3D reconstruction. Material and methods: We performed en‐bloc removal of the entire pelvis of three male human fetuses between 18 and 40 weeks. Serial whole mount sections (5 μm intervals) were stained and investigated. The sections were stained with Masson's trichrome and Eosin Hematoxylin, and immunostained with: anti‐SMA antibody for smooth muscle; anti‐S100 antibody for all nerves; and anti‐PMP22 antibody, anti‐TH antibody, anti‐CGRP antibody, anti‐NOS antibody for somatic, adrenergic, sensory and nitrergic nerve fibers, respectively. The slides were digitized for 3D reconstruction to improve topographical understanding. An animated reconstruction of the autonomic innervation of the US was generated. Results: The external and internal US are innervated by autonomic nerves of the inferior hypogastric plexus (IHP). These nerves are sympathetic (positive anti‐TH antibody), sensory (positive anti‐CGRP antibody), and nitrergic (positive anti‐NOS antibody). Some autonomic fibers run within the neurovascular bundles, posterolaterally. Others run from the IHP to the posteromedial aspect of the prostate apex, above an through the rectourethral muscle. The external US is also innervated by somatic nerves (positive anti‐PMP22 antibody) arising from the pudendal nerve, joining the midline but remaining below the rectourethral. Conclusions: This study provides anatomical evidence of an autonomic component in the innervation of the external US that travels in the neurovascular bundle. During radical prostatectomy, the rectourethral muscle and the neurovascular bundles are to be preserved, particularly during apical dissection.